Assessment of skill gap and factors influencing career choice among fisheries graduates in India - Green Sea, K.; Krishnan, M.; Saravanakumar, V.; prakash, Swadesh; Ananthan, P. S.; Qureshi, Neha (Indian Journal of Fisheries, 2017)
The paper reports the result of an assessment of career choice among fisheries graduates and skill gap between expectations of employers employees in India. Qualitative and quantitative data were collected from the fisheries students (employees) and employers through survey. The results revealed that there are differences between factors influencing career choice of males and females with reference to two factors namely, previous job experience and family status. The employers employees survey revealed that there exists a gap in technical skills which should be given focus to increase competency among employees to match the expectations of the employer. There is an indication of emerging demand for fisheries professionals to cater the needs of employers in fisheries sector.